Engaging Students in Information Literacy: Curriculum Planning from the Ground Up - Given, Lisa; Julien, Heidi (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This project examines students’ experiences as they complete high school, to assess information literacy preparation for further study in post-secondary environments. This presentation examines results from the first phase of a longitudinal project (i.e., information literacy skills tests with 103 grade 12 students and a sample of individual interviews). Ce projet examine l'expérience des élèves à la fin des études secondaires dans le but d'évaluer leur niveau de préparation quant à la maîtrise de l'information en vue d'études postsecondaires. Seront présentés les résultats de la première phase de ce projet longitudinal (c'est-à-dire un test d'aptitude de maîtrise de l'information auprès de 103 élèves de 12e année et quelques extraits d'entrevue).